Could the Age Difference of a Single Calendar Year between Patients Undergoing IVF at 34, 35 or at 36 Years Old Affect the IVF Outcome? A Retrospective Data Analysis - Pantos, Konstantinos (Medicina (Kaunas), 2020)
Background and Objectives: Clinicians are called to overcome age-related challenges in decision making during In Vitro Fertilization (IVF) treatment. The aim of this study was to investigate the possible impact of a single calendar year difference among patients aged 34, 35 and 36 on IVF outcomes. Materials and Methods: Medical records between 2008 and 2019 were analyzed retrospectively. The study group consisted of women diagnosed with tubal factor infertility. Sample size was divided in three categories at 34, 35 and 36 years of age. Embryo transfer including two blastocysts was performed for every patient. Comparisons were performed regarding hormonal profile, response to stimulation, quality of transferred embryos, positive hCG test and clinical pregnancy rate. Results: A total of 706 women were eligible to participate. Two-hundred and forty-eight women were 34, 226 were 35 while the remaining 232 were 36 years old. Regarding the hormonal profile, the number of accumulated oocytes and the quality of embryos transferred, no statistically significant difference was documented between the three age groups. Women aged 34 and 35 years old indicated a significantly increased positive hCG rate in comparison to women aged 36 years old (p-value = 0.009, p-value = 0.023, respectively). Women aged 34 and 35 years old presented with a higher clinical pregnancy rate in comparison to those aged 36 years old (p-value = 0.04, p-value = 0.05, respectively). Conclusion: A calendar year difference between patients undergoing IVF treatment at 34 or 35 years of age does not appear to exert any influence regarding outcome. When treatment involves patients above the age of 35, then a single calendar year may exert considerable impact on IVF outcome. This observation indicates that age 35 may serve as a valid cut-off point regarding IVF outcome.